2003
DOI: 10.1046/j.1365-2265.2003.01895.x
|View full text |Cite
|
Sign up to set email alerts
|

Residual goitre in the postiodization phase: iodine status, thiocyanate exposure and autoimmunity

Abstract: Persistent, albeit reduced prevalence of goitre, despite adequate iodine prophylaxis, suggests existence of additional factors in goitrogenesis in India. Thyroid autoimmunity can explain only a part of the goitre prevalence. The role of goitrogens in residual goitre prevalence is brought forth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
77
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 30 publications
8
77
2
1
Order By: Relevance
“…In contrast, subjects from an equal number of villages had a much lower goitre prevalence of 29 %, albeit higher than the internationally acceptable norm, despite UIC levels showing unsatisfactory iodine nutrition. This heterogeneous picture could in part be explained by: (i) a possible contribution of thiocyanate and other goitrogens as reported previously from the same area (22) ; and (ii) single point analysis may not reflect the USI failure at earlier times (13) .…”
Section: Discussionmentioning
confidence: 81%
“…In contrast, subjects from an equal number of villages had a much lower goitre prevalence of 29 %, albeit higher than the internationally acceptable norm, despite UIC levels showing unsatisfactory iodine nutrition. This heterogeneous picture could in part be explained by: (i) a possible contribution of thiocyanate and other goitrogens as reported previously from the same area (22) ; and (ii) single point analysis may not reflect the USI failure at earlier times (13) .…”
Section: Discussionmentioning
confidence: 81%
“…Increased iodine intake in diet, presence of goitrogens in diet as reported from studies in India, deficiency of micronutrients like selenium and iron, are some of the reasons for high Hypothyroidism prevalence in India. [16][17][18] …”
Section: Discussionmentioning
confidence: 99%
“…Increased iodine intake in diet, presence of goitrogens in diet as reported from studies in India, deficiency of micronutrients like selenium and iron are some of the reasons ascribed to high hypothyroidism prevalence in India. [19][20][21] An inter-relation of this high prevalence of thyroid disorders with a high prevalence of the other major endocrinopathy diabetes mellitus has to be explored further. Prevalence of hyperthyroidism, both overt and subclinical in various studies has been reported to be around 1%.…”
Section: Discussionmentioning
confidence: 99%